It pays to partner with a firm that writes annual reports well ✰ - Baxamusa, Mufaddal; Jalal, Abu; Jha, Anand (Journal of Banking & Finance, 2018)
We use strategic alliances as a setting to examine whether the readability of a firm's partner's 10-K matters. We find that the increase in the cumulative abnormal return (CAR) around the announcement of an alliance is relatively lower when the firm's partner in a strategic alliance has a less readable 10-K report. Additional tests show that the impact of the readability of a partner's 10-K is much stronger when investors suspect insufficient due diligence before the alliance's formation, when the partner is from a different industry, and when the alliance occurs before the Sarbanes–Oxley Act. Overall, our results show that the readability of a partner's annual report matters—it pays to partner with a firm that writes these reports well.